Wild girl - Skelton, Helen, 1983- (Candlewick Press, 2020)
TV presenter Helen Skelton presents six outdoor adventures in some of the world's most extreme wilderness, and describes a guide for girls to have adventures of their own no matter where they are. Features information about the places she travels to and the training Skeleton underwent to prepare for her travels, and highlights famous women explorers and adventurers. Includes color photographs and illustrations.